Unveiling the Evidence of Utilizing Sexual and Reproductive Health Services, Knowledge Deficits and Restriction Concerns of Indigenous and Women Living with HIV and AIDS in Nepal: A Scoping Review - Anup Adhikari; Bhagwan Aryal; Gyanu Maharjan; Punya Shori Suwal (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This scoping review aimed to understand Sexual and Reproductive Health and Rights (SRHR) concerns among the Indigenous and ‘Women Living with Human Immunodeficiency Virus’ (HIV) (WLWH) in Nepal. It identified various concerns, some of which focused on Indigenous peoples or groups and others that required community involvement. The review included an analysis of 150 articles from various platforms, of which 60 were selected for review. It focused on research papers, policy documents, and fact sheets (excluding school-based studies) from 2000 to 2023, emphasizing 2011 to 2020. Established scholars guided the methodology, significantly contributed to existing knowledge, and informed future research directions in the critical area of SRHR of People Living with HIV and AIDS (PLHA) and indigenous people. The review revealed cultural, structural, and gender-based issues that affect access to SRHR services. The indigenous populations were discriminated against and had low access to services. There was widespread stigma and violence, which are very determinant to the health and well-being of women. The synthesis reveals the necessity of specific interventions to advance knowledge dissemination and build autonomy to manage the complex problems affecting indigenous and WLWH in Nepal. Results from the scoping review identified barriers to accessing services and obtaining SRHR information among Indigenous WLWH: they live in remote areas, many do not know about their SRHR, few have access to services, and many experience financial barriers. Thus, a targeted intervention needs to be created (and knowledge dissemination improved) to help mitigate the denial of rights experienced by this group.